Elemental changes in heart and coronaries after breast cancer radiotherapy assessed by synchrotron radiation soft X-ray spectromicroscopy. Issue 1 (1st September 2022) - Pickler, A; Mendes, G; Tanure, T; Serqueira, L; Sena, G; Fidalgo, G; Colaço, M; Muñoz, E; Ferreira-Machado, S; Lau, C C; Salata, C; Mantuano, A; et al.
Abstract: Radiotherapy (RT) plays a pivotal role in the treatment of breast cancer (BC) and various thoracic malignancies. Radiation induced heart disease (RIHD) is one such long term toxicity which can offset the improvement in cancer specific mortality. Long term normal tissue toxicity is becoming a bigger concern, as early diagnosis and the improvement in the treatment of these cancers has led to patients surviving longer. Our research group on Physics applied to biomedical sciences has been investigating the side effects of BC treatment (RT and chemotherapy) for more than ten years. The cardiac regeneration has been studied to better understand the damage that occurs following radiation procedures in the heart tissue after many thoracic cancer treatments. One possible complication is coronary artery disease induced by irradiation after radiotherapy in thoracic area. Studies on the structures of cardiac tissue and the distribution of low atomic weight element can help to understand mechanisms associated with damage to healthy tissue, as these are of fundamental importance to metabolism in biological systems. The present study aimed to elucidate how radiotherapy in the thoracic area causes damage in the coronary artery, and to verify the potential use of losartan in reducing, or even preventing, the side effects of irradiation in this artery. To assess elemental and morphological differences in aortic and coronary samples, the Low Energy X-Ray Fluorescence (LEXRF) technique using Synchrotron Radiation was employed. SR- LEXRF and scanning transmission X-ray microscopy measurements were carried out at the beamline TwinMic at Elettra Sincrotrone Triste, Italy.